2016
DOI: 10.1016/j.bjane.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of intra-arterial sugammadex and dexmedetomidine: an experimental study

Abstract: Administration of sugammadex and dexmedetomidine to rabbits by intra-arterial routes caused histological arterial damage. To understand the histological changes caused by sugammadex and dexmedetomidine more clearly, more experimental research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…An experimental animal study involving sugammadex is included. 37 The presentation, time sequence, and complications of injuries caused by illicit intra-arterial injections and iatrogenic injuries suggest a similar pathophysiology and it may be possible to extrapolate the evaluation of injury severity and treatment options derived from one group to the other.…”
Section: Summary Recommendationsmentioning
confidence: 99%
“…An experimental animal study involving sugammadex is included. 37 The presentation, time sequence, and complications of injuries caused by illicit intra-arterial injections and iatrogenic injuries suggest a similar pathophysiology and it may be possible to extrapolate the evaluation of injury severity and treatment options derived from one group to the other.…”
Section: Summary Recommendationsmentioning
confidence: 99%
“…In this study, while no histopathological effect was observed in the control group and low-dose (2 mg/kg) sugammadex group, the necrotic changes observed in the high-dose (16 mg/kg) group lead us to consider that the effect is linked to the dose used. In a previous study, Hanci et al (20) administered sugammadex intraarterially at a dose of 4 mg/kg in rabbits and they reported signifi cant histopathological changes in arterial endothelial structure due to endothelial damage compared to the control group. Hence, we decided to investigate the effects of sugammadex doses of 2 mg/kg and 16 mg/kg to create a dose-response curve.…”
Section: Discussionmentioning
confidence: 98%